Influence of AM Fungi on Physiological Changes in Terminalia arjuna L. : an Endangered Tree of Indian Thar Desert - Bohra, Avinash; Mathur, Nishi; Bohra, Sachendra; Singh, Joginder; Vyas, Anil (Indian Forester, 2007)
The efficiency of eight arbuscular mycorrhizal species collected from rhizosphere soil of Terminalia arjuna L. from Indian Thar desert was tested. Mycorrhizal colonization resulted in increased accumulation of nutrients, chlorophyll, carotenoids, sugars and proteins. Among the eight AM fungi used, Glomus fasciculatum (Thaxter sensu Gerd.) Gerd. & Trappe proved to be the most efficient.